2012
DOI: 10.1016/j.ajem.2010.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Framingham risk factors among ED patients with newly diagnosed atrial fibrillation

Abstract: Study Objective Atrial fibrillation (AF) is often first diagnosed in the emergency department (ED) and accounts for nearly 1% of all ED visits. Our objective was to assess the Framingham Heart Study risk score for AF development in ED patients with newly diagnosed AF. Methods We systematically reviewed the electronic medical records of ED patients with newly diagnosed AF between August 2005 and July 2008. We measured the frequency of the Framingham Heart Study predictors and calculated each patient's risk sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…[6,7] We have previously reported that these risk factors are present in many ED patients with newly diagnosed AF. [8] Nearly all of the Framingham risk factors are routinely identified during an ED visit including patient age, sex, SBP, home antihypertensive treatment and PR interval (if an ECG is performed). BMI and ages of significant cardiac murmur and heart failure diagnosis might be less reliably documented in the ED record.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6,7] We have previously reported that these risk factors are present in many ED patients with newly diagnosed AF. [8] Nearly all of the Framingham risk factors are routinely identified during an ED visit including patient age, sex, SBP, home antihypertensive treatment and PR interval (if an ECG is performed). BMI and ages of significant cardiac murmur and heart failure diagnosis might be less reliably documented in the ED record.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed methodology of the original study has been previously reported. [8] Briefly, adult patients with a primary or supporting International Classification of Disease, Ninth Edition ED diagnosis of AF between August 1, 2005 and July 31, 2008 were eligible for inclusion in the original cohort. Inclusion criteria required documented evidence of AF or atrial flutter on an electrocardiographic (ECG) or rhythm strip.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation